Ultrasonic-assisted Cr3C2 nanoparticle-reinforced aluminum-copper plasma arc brazing process - Congcong Lu; Yuhang Xie; Xiaoquan Yu; Yan Li; Jiankang Huang; Ding Fan (Journal of Materials Research and Technology)
The welding of aluminum and copper can show the comprehensive performance of both materials. However, welding these two metals faces challenges because of their different physical and chemical properties. A plasma arc brazing with ultrasonic assisted nanoparticles was proposed to join these two metals and control the interfacial microstructure. The microstructure, mechanical properties, and electrical properties of the joints were analyzed using a combination of scanning electron microscopy, X-ray diffraction, electron backscatter diffraction, etc. The formation mechanism of the IMC layer was also explored. The results revealed that the combination of Cr3C2 nanoparticles and ultrasound exerted a synergistic effect, the weld bead formed well, with significantly improved spreading ability of liquid aluminum and wettability on the copper side. The combined effect of ultrasound and nanoparticles fragmented the intermetallic compound layer and effectively suppressed its further growth, the average reduction in IMC layer thickness was 35.5%. Additionally, the average grain size of the welded joints decreased from 7.4 μm to 5.4 μm, showing a noticeable grain refinement effect. In terms of mechanical properties, the joint's tensile strength increased by 115.21%, and its relative electrical conductivity improved by 35.64%, significantly enhancing both the mechanical strength and electrical conductivity of the joint.